Demographic trends in the Ottoman Empire in Europe and their impact on economy: neither the West, nor the East - Moačanin, Nenad (2007)
The aim of the relazione is to put emphasis on the relatively limited participation of the core lands of Ottoman Balkans in the economy of Europe. Unlike much of Central and Eastern Europe where export-oriented production of foodstuffs became dominant, here the very nature of the Ottoman system prevented such a development. The areas under Ottoman control that played important role in supplying German and partly Italian towns with livestock, were not subject to the direct rule of the sultan (the case of the Danubian principalities). Even Central Hungary, where this was the case, cannot be ranked among typical Ottoman provinces. On the other hand, oscillations of the population size in the Early Modern Ages show absence of strong upward or downward tendencies. The rather widespread belief in a „ population pressure“ in the earlier period as well as in „ heavy population losses“ thereafter, which might suggest that the Balkans belonged to the common pattern of development like the lands in the Western Mediterranean world, is anchored in misinterpretation of the Ottoman tax records. Thus the basic precondition for transformations in economy similar to those in the rest of Europe was nearly completely lacking.
Projekt MZOS
ENG